Extending Validity of the Bacterial Cell Cycle Model through Thymine Limitation: A Personal View - Arieh Zaritsky (Life, 2023)
The contemporary view of bacterial physiology was established in 1958 at the “Copenhagen School”, culminating a decade later in a detailed description of the cell cycle based on four parameters. This model has been subsequently supported by numerous studies, nicknamed BCD (The Bacterial Cell-Cycle Dogma). It readily explains, quantitatively, the coupling between chromosome replication and cell division, size and DNA content. An important derivative is the number of replication positions n, the ratio between the time C to complete a round of replication and the cell mass doubling time τ; the former is constant at any temperature and the latter is determined by the medium composition. Changes in cell width W are highly correlated to n through the equation for so-called nucleoid complexity NC (=(2n − 1)/(ln2 <semantics>×</semantics> n)), the amount of DNA per terC (i.e., chromosome) in genome equivalents. The narrow range of potential n can be dramatically extended using the method of thymine limitation of thymine-requiring mutants, which allows a more rigorous testing of the hypothesis that the nucleoid structure is the primary source of the signal that determines W during cell division. How this putative signal is relayed from the nucleoid to the divisome is still highly enigmatic. The aim of this Opinion article is to suggest the possibility of a new signaling function for nucleoid DNA.